2022
DOI: 10.1021/acs.est.2c05781
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Use of Sustainable Aviation Fuel to Maximize Climate Benefits

Abstract: Sustainable aviation fuel (SAF) can reduce aviation's CO 2 and non-CO 2 impacts. We quantify the change in contrail properties and climate forcing in the North Atlantic resulting from different blending ratios of SAF and demonstrate that intelligently allocating the limited SAF supply could multiply its overall climate benefit by factors of 9−15. A fleetwide adoption of 100% SAF increases contrail occurrence (+5%), but lower nonvolatile particle emissions (−52%) reduce the annual mean contrail net radiative fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…The RF results, shown in table 1, comprise longwave (LW), shortwave (SW) and net (LW + SW) annual mean global instantaneous contrail RF values, as well as their percentage differences with respect to the MH97's base case. The cases combine scaled IWC values with the two described PSD schemes, amongst which N ice values differ by around 85% at representative persistent contrail temperatures, emulating plausible differences between contrails and natural cirrus [30], as well as possible soot reductions linked to a prospective introduction of SAF.…”
Section: Resultsmentioning
confidence: 99%
“…The RF results, shown in table 1, comprise longwave (LW), shortwave (SW) and net (LW + SW) annual mean global instantaneous contrail RF values, as well as their percentage differences with respect to the MH97's base case. The cases combine scaled IWC values with the two described PSD schemes, amongst which N ice values differ by around 85% at representative persistent contrail temperatures, emulating plausible differences between contrails and natural cirrus [30], as well as possible soot reductions linked to a prospective introduction of SAF.…”
Section: Resultsmentioning
confidence: 99%
“…It has been argued that SAF represents a significant opportunity to co-mitigate contrails and contrail cirrus with reduced aromatic content fuels. 201 Equally, it would be possible to hydrotreat fossil fuels to remove the aromatic components and S. This would have an associated energy expenditure (see Section 6.1) 195 but would nonetheless be possible. Both proposals remain problematic and uncertain, since the contrail-forming potential in the low soot emission regime (<10 14 particles per kg fuel) at low temperatures is unknown although modelling suggests an increase.…”
Section: Non-co2 Effects and Their Relationships To Future Fuelsmentioning
confidence: 99%
“…More recently, it has been suggested that such SAF (which, at present is limited in quantity) might be deployed more effectively in combination with a prediction of contrails, such as outlined in Section 8.3. Such an approach may be effective 201 but the approach would need to solve the ongoing difficulties of predicting ISSRs and the assumed benefit of SAF on contrail forcing needs to be unambiguously demonstrated, which is unclear because of the lack of explicit consideration of volatile particles at low soot numbers (see Kärcher, 2018). 110…”
Section: Tradeoffs Between Emissions and Their Effectsmentioning
confidence: 99%
“…ASTM, the fuel standardization body responsible for standardizing aviation fuels, has approved eight different production routes for synthetic hydrocarbons (ASTM D7566), which are currently permitted to be blended with at least 50% fossil kerosene (ASTM D1655) to provide an approved aviation fuel. Such fuel blends can therefore already save up to 50% of the fuel-related CO 2 emissions and can contribute additionally to reducing non-CO 2 effects. These drop-in fuels acknowledged by ASTM can be renewable fuels from a nonbiological origin (RFNBO) or from a biogenic source. RFNBOs use electrical energy provided by systems using renewable sources of energy as well as a nonbiogenic carbon source (excluding biogenic CO 2 ) to produce hydrocarbons .…”
Section: Introductionmentioning
confidence: 99%